Coexistent Dedifferentiated Endometrioid Carcinoma of the Uterus and Adenocarcinoma of the Bladder in Lynch Syndrome: Case Report and Review of the Literature. Issue 3 (March 2020) - Groth, John V.; Prabhu, Sanjiv; Periakaruppan, Ramayee; Ohlander, Samuel; Emmadi, Rajyasree; Kothari, Rajul
Abstract : Lynch syndrome is an autosomal dominant disorder, caused by an abnormality in DNA mismatch repair genes and characterized by the development of a variety of cancers. Upper urinary tract urothelial carcinoma is well characterized in Lynch syndrome; however, support for the inclusion of bladder urothelial carcinoma is limited, except for MSH2 mutation carriers. Urologic adenocarcinoma has not been documented in Lynch syndrome. Here we report, to the best of our knowledge, the first case of bladder adenocarcinoma, synchronous with uterine endometrioid dedifferentiated endometrioid adenocarcinoma in a patient with Lynch syndrome. We present a 47-year-old woman with an MLH1 gene mutation (G133X 397G>T) who presented with menorrhagia. Eleven family members have this mutation, 6 with carcinoma: 5 colorectal and 1 with a gynecologic primary of unknown type. Colonoscopy and endoscopy were unremarkable. Positron emission and computed tomography revealed a 3 cm anterior dome bladder mass without additional extrauterine disease or uterine connection. She underwent partial cystectomy, laparoscopic hysterectomy, bilateral salpingo-oophorectomy, and lymphadenectomy. The uterus demonstrated a dedifferentiated endometrioid adenocarcinoma, immunohistochemically positive for vimentin, ER, CK7, MSH2, MSH6, and p53 (focally) and negative for CEA, CDX2, CK20, β-catenin, MLH1, and PMS2. The bladder demonstrated a well-differentiated, enteric-type adenocarcinoma without muscularis propria invasion, positive for CEA, CDX2, CK20, p53, MSH2, and MSH6 and negative for vimentin, ER, CK7, MLH1, and PMS2. Eleven nodes were negative for carcinoma. The morphologic, immunohistochemical, and clinical findings support synchronous bladder adenocarcinoma, enteric type, and uterine dedifferentiated endometrioid adenocarcinoma, in a patient with Lynch syndrome.